Middle school ELL and LD teachers' perceptions of the importance of reading methods - Lee, Pei-Yi (Kansas State University, 2007)
This study is a follow-up to Al-Fadda's (2004) investigation of middle school teacher's perceptions of the importance of reading methods. The primary research question to be addressed in this study was: What are ELL and LD teachers' perceptions of the importance of specific reading strategies for their respective types of students? To address this question the researcher developed a survey with five demographic questions and 44 reading methods based on the framework of the COBRA model developed by Heerman (2002). The researcher administered the survey to public middle and junior high school ELL and LD teachers from Kansas, New Mexico, Oklahoma, and Texas and compared the two groups' perceptions of the importance of several reading strategies. Analysis of the results showed that there was a 60% agreement rate between the two teacher groups (no significant differences) for three of the COBRA goals (background knowledge, comprehension, and study and application) and a 40% difference rate between the two teacher groups (significant differences) for two of the COBRA goals (experiential learning and vocabulary). For the 44 survey items, there was an agreement rate of 82.82%, and a difference rate of 17.18%. The researcher concludes that there were more similarities than differences between ELL teachers' and LD teachers' perceptions of the importance of the surveyed reading methods, however, there were also real differences. The researcher found justification for the belief that ELL and LD teachers should be considered specialist teachers when it comes to rating the relative importance of reading methods. ELL teachers appear to be inclined to use reading methods related to language, experience, and vocabulary methods. The results also reveal that LD teachers appear to be inclined to use reading methods related to intervention strategies with conferencing, coaching, compensatory methods, specific skills development and memory processes. In addition, the researcher noted a large number of methods with small mean differences, showing the certain levels of agreement between the two teacher groups. In terms of the five teacher variables, percentage of ELL students, percentage of low-income students and school enrollment proved to be the least active variables but the teacher variables of teachers' education levels and teachers' experience levels were more active.
Keywords: Curriculum and Instruction; Reading Methods; ELL or English Language Learner; LD or Learning Disability; Middle School Teachers; COBRA; Education, Curriculum and Instruction (0727)